Reflective Journaling for English as a Foreign Language (EFL) Teachers in Japan - Brent Allen Jones (Journal of ELT, Linguistics, and Literature, 2015)
This paper reports on the initial phase of a qualitative investigation into reflective journaling as a form of professional development (PD) involving EFL teachers at universities in Japan. The research questions were: (1) What shared/differing concerns or challenges are experienced by university EFL teachers in Japan? (2) Is reflective journaling a viable form of professional development for EFL teachers in Japan? Preliminary analysis identified classroom management, questioning of one’s own perspectives/practices, and classroom community as shared concerns. Also, with appropriate support, reflective journaling appears to be a viable form of PD for in-service teachers of EFL in this context.